2022
DOI: 10.1007/s12325-022-02259-2
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Ovarian Cancer with BRCAness Phenotype: A Treatment Challenge

Abstract: Introduction Ovarian cancer is a leading cause of death among women with gynecologic malignancies. The relapse rate is high after platinum-based therapy, with the effectiveness of subsequent treatment lines decreasing over time. Recent data suggest the benefit of maintenance therapy with niraparib in platinum-sensitive recurrent disease. Case Presentations We report a case series of five women with advanced ovarian cancer and BRCAness phenotype who responded favorably, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…With the development of clinical trials, a series of high-level evidence-based medical evidence has shown that maintenance therapy with PARP inhibitors after initial treatment of OC or platinum-sensitive relapsed therapy achieved complete response (CR) or partial response (PR) can signi cantly prolong PFS in patients [50,51]. The exact mechanism is not clear, but it may be related to "capture", that is, PARP inhibitors bind to the niacinamide adenine dinucleotide binding pocket of PARP1/2, forming conformational abnormalities that stabilize DNA-PARP [52][53][54]. Here, we illustrate a new function of PARP1 that is different from the common HR repair function [44,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of clinical trials, a series of high-level evidence-based medical evidence has shown that maintenance therapy with PARP inhibitors after initial treatment of OC or platinum-sensitive relapsed therapy achieved complete response (CR) or partial response (PR) can signi cantly prolong PFS in patients [50,51]. The exact mechanism is not clear, but it may be related to "capture", that is, PARP inhibitors bind to the niacinamide adenine dinucleotide binding pocket of PARP1/2, forming conformational abnormalities that stabilize DNA-PARP [52][53][54]. Here, we illustrate a new function of PARP1 that is different from the common HR repair function [44,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer is one of the most common cancers and a leading cause of mortality among women [1]. It is often diagnosed at an advanced stage, resulting in poor health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…All qualities (tumor stage, tumor subtype and quantitatively measuring tumor heterogeneity) are essential principles that guide the treatment decision-making process and shape the direction of clinical research [ 33 ]. Moreover, molecular and genetic features, including germline and somatic breast cancer 1 (BRCA1) and breast cancer 2 (BRCA2) mutations [ 34 , 35 ], may influence the prognosis of patients [ 36 , 37 ], the recurrence rate [ 38 ], and the cancer response to DNA-damaging agents, such as platinum chemotherapy [ 39 ], or DNA repair pathways inhibitors. Poly-ADP-ribose polymerase inhibitors (PARPi) have recently shown to be effective as a first-line or maintenance treatment for patients with advanced BRCA-mutated ovarian cancer [ 40 ].…”
Section: Introductionmentioning
confidence: 99%